38. SATISFACTION OF PARENTS OF CHILDREN FROM 9 - 36 MONTHS USING RESPIRATORY PHYSICAL THERAPY SERVICES AT HQT REHABILITATION CENTER IN 2023 AND SOME RELATED FACTORS (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the satisfaction of parents of children aged 9-36 months using respiratory physical therapy services and some factors related to the satisfaction of parents of children at the Healthy Quality and Thankful (HQT) rehabilitation center in 2023. Method: Analytical cross-sectional descriptive study. Result: The overall satisfaction rate of the research subjects with the service used was relatively high at 86,4%, the remaining 13,6% were not satisfied with the service. In particular, the satisfaction rate for 5 keys next to “accessibility”, “facilities”, “information transparency”, “staff attitude”, and “treatment results” are 60%, 77,4%, 80,7%, 90,2% and 90,0%. Analysis results show that service satisfaction is related to: gender (OR=2,66; 95%CI=1,3-5,19), average income (OR=1,79; 95%CI=1,02-3,13), type of treatment before respiratory physical therapy and frequency of respiratory physical therapy (OR=6,67; 95%CI=1,31-33,87). Conclusion: The overall satisfaction rate of the research subjects with the service used was relatively high at 86,4%. Factors related to overall service satisfaction with statistical significance p
Keywords: Patient satisfaction, respiratory physiotherapy, HQT Hanoi.